Bone mineral content determined by energy X-ray absorptiometry correlates with handgrip strength in Latin American divers - Alex Véliz; Raquel Pereira; Anita Dörner; Cristian Álvarez (Frontiers in Public Health, 2025)
IntroductionAlthough a lack of gravitational stimuli decreases bone mineral content in some populations, such as astronauts’ bone mineral content (BMC), little is known about the association of BMC with handgrip muscle strength (HGS) in divers of different years of diving experience.ObjectivesTo describe the BMC and body composition of diver workers of different years of diving experience. A second objective was to associate the level of BMC with HGS.Materials and methodsA descriptive and longitudinal pilot study was carried out in adult men divers of different years of diving experience; tertile 1 of diving experience 1–20 years (T1DE, n = 27), tertile 2 of diving experience 21–35 years (T2DE, n = 11), and tertile 3 of diving experience 36–45 years (T3DE, n = 17). Primary variables were BMC, total fat-free mass (FFM), and total body fat mass (BF), which were analyzed using dual X-ray absorptiometry (iDXA) equipment and the average of both arms’ handgrip strength (HGSav). Secondary variables were lifestyle patterns, anthropometry, and other socio-demographic variables.ResultsT3DE showed significant differences vs. T1DE group in BMCLegs (diff. −107.9 g, p = 0.029), BMCRL (diff. −51.4 g, p = 0.039), and BMCLL (diff. −55.7 g, p = 0.037). T3DE showed significant differences vs. T1DE group in outcomes total FFM (diff. −5011.9 g, p = 0.015), FFMArms (diff. −1275.1 g, p = 0.009), FFMRA (diff. −472.3 g, p = 0.012), FFMLA (diff. −406.6 g, p = 0.028), FFMLegs (diff. −2117.8 g, p = 0.031), FFMRL (diff. −1046.3 g, p = 0.037), and FFMLL (diff. −1071.3 g, p = 0.031). There was a significant correlation between HGSav and total BMC (R2 = 21.3%), between HGSRA and total BMC (R2 = 21.1%), between HGSLA and total BMC (R2 = 20.2%), between HGSav and BMCArms (R2 = 28.8%), between HGSRA and BMCArms (R2 = 27.9%), between HGSLA and BMCArms (R2 = 27.8%), between HGSav and BMCLegs (R2 = 13.3%), between HGSRA and BMCLegs (R2 = 13.8%), and between HGSLA and BMCLegs (R2 = 11.9%).ConclusionDiver workers with greater years of experience exhibit a reduced level of BMC and FFM in the legs compared to peers with less experience, and HGS is associated with BMC. Future longitudinal studies in diver workers could explore BMC and body composition in these populations to confirm our findings and include other physical fitness parameters in different diving specialties.